Effective leadership in adventure programming - Priest, Simon, ....-; Gass, Michael A., ....- (Champaign, IL : Human Kinetics, 2005)
Effective Leadership in Adventure Programming, Second Edition, will help students •understand the key elements of effective leadership in both theory and practice, •learn important leadership skills through real-world applications, and •explore new trends in adventure programming. Effective Leadership in Adventure Programming, Second Edition, explains how the key elements of leadership work in theory and practice, and it helps train the next generation of adventure leaders—training that is paramount to developing the field. Through this text, readers will enhance their understanding of this rapidly growing profession. Renowned authors Simon Priest and Michael Gass provide in-depth descriptions and real-world applications of the technical, organizational, instructional, and facilitative skills that are essential to adventure leadership. The authors also identify what they call the metaskills that superior leaders use to combine the other essential skills seamlessly and effectively. The authors provide fully updated content and references, including new information on legal liability, risk management skills, and future research trends in adventure programming. They also do the following: •Examine the historical and philosophical foundations of adventure programming •Provide safety and environmental guidelines that leaders should follow •Describe the organizational, instructional, and facilitation skills that outdoor adventure leaders should possess •Identify the importance of flexible leadership style, problem-solving and decision-making skills, experience-based judgment, effective communication, and ethical behaviors The first edition of this book set new levels of excellence in leadership in adventure programming. The second edition preserves the comprehensive and classic nature of the original while raising the standard for the field in the 21st century. The authors' skillful approach to integrati
Includes bibliographical references and indexes.
Keywords: Buitensporten; Ervaringsleren; Leidinggeven